Study of factors influencing Job Satisfaction among healthcare professionals - a quantitative explanation - Sawhney, Deepti (Digital Repository of Theses, 2025)
Job satisfaction among healthcare professionals is a critical factor influencing not only individual well-being but also organizational efficiency, patient care quality, and overall healthcare outcomes. This quantitative study aims to investigate the key factors influencing job satisfaction among healthcare professionals, including doctors, nurses, and allied healthcare staff. Using a structured survey method, data was collected from 250 healthcare professionals working in both public and private healthcare settings. The survey instrument incorporated validated scales to measure various determinants such as work environment, compensation, professional growth opportunities, leadership support, work-life balance, and interpersonal relationships at the workplace. The collected data were analyzed using descriptive statistics, correlation analysis, and multiple regression models to identify the most significant predictors of job satisfaction. The findings reveal that work environment and leadership support have a strong positive correlation with job satisfaction, while factors such as excessive workload and lack of professional development opportunities negatively influence job satisfaction levels. Interestingly, intrinsic factors such as personal accomplishment and recognition were found to have a more profound impact compared to extrinsic factors like salary. This study underscores the importance for healthcare administrators and policymakers to foster supportive work environments, ensure fair workload distribution, and create opportunities for continuous professional development to enhance job satisfaction among healthcare professionals. Addressing these areas not only aids in reducing turnover rates but also contributes to improved patient outcomes and organizational sustainability. The study concludes by recommending strategies for healthcare organizations to enhance job satisfaction, thus ensuring a motivated and efficient healthcare workforce.